PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK MATERI BENTUK ALJABAR UNTUK MENINGKATKAN LITERASI SISWA - Melinda Rismawati; Marli Hidayat; Anggista Septiani Saputri; Rupinus Isa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
The research results obtained are variations in the contribution of urea used as fillers is 15%. Based on this research, it can be said that diaper waste has the potential to control the release of urea. Furthermore, it can explain the rate of release of urea in chili plants. The purpose of this research is to develop comic-based teaching materials in algebraic forms to improve students' literacy skills. this research method is research and development (Research and Development). In developing teaching materials, researchers use 6 stages, namely (1) analyzing the product to be developed, (2) making comic scripts, (3) developing initial products, (4) expert validation and revision, (5) field trials and product revisions, and (6) manufacture of the final product. The subjects of this study consisted of expert validators, teachers and students of class X IPS 1 SMAN 1 Sintang which consisted of 20 people. The instruments used are validation, questionnaires, and questions. Based on the research, the results of the media and material validation have very feasible interpretation criteria of 86.36%, the teacher's response results have an interesting interpretation criterion of 75%, the results of the student response questionnaire have an interesting interpretation criterion of 79.75%. The conclusion of this research is; Mathematical literacy ability of students of class X IPS 1 SMAN 1 Sintang is high with an average value of 71.08%. Comics teaching materials can improve the mathematical literacy skills of high school students.